Screening of two-photon activated photodynamic therapy sensitizers using a 3D osteosarcoma model. Issue 9 (27th March 2019) - Dobos, Agnes; Steiger, Wolfgang; Theiner, Dominik; Gruber, Peter; Lunzer, Markus; Van Hoorick, Jasper; Van Vlierberghe, Sandra; Ovsianikov, Aleksandr
Abstract : An in vitro screening platform for high-throughput profiling and comparison of two-photon photodynamic therapy sensitizers was established. Abstract : Photodynamic therapy (PDT) involves a photosensitizing agent activated with light to induce cell death. Two-photon excited PDT (TPE-PDT) offers numerous benefits compared to traditional one-photon induced PDT, including an increased penetration depth and precision. However, the in vitro profiling and comparison of two-photon photosensitizers (PS) are still troublesome. Herein, we report the development of an in vitro screening platform of TPE-PS using a 3D osteosarcoma cell culture. The platform was tested using three different two-photon (2P) active compounds – a 2P sensitizer P2CK, a fluorescent dye Eosin Y, and a porphyrin derivative (TPP). Their 2P absorption cross-sections ( σ 2PA ) were characterised using a fully automated z -scan setup. TPP exhibited a remarkably high σ 2PA at 720 nm (8865 GM) and P2CK presented a high absorption at 850 nm (405 GM), while Eosin Y had the lowest 2P absorption at the studied wavelengths (<100 GM). The cellular uptake of PS visualized using confocal laser scanning microscopy showed that both TPP and P2CK were internalized by the cells, while Eosin Y stayed mainly in the surrounding media. The efficiency of the former two TPE-PS was quantified using the PrestoBlue metabolic assay, showing a significant reduction in cell viability after two-photon irradiation. The possibility of damage localization was demonstrated using a co-culture of adipose derived stem cells together with osteosarcoma spheroids showing no signs of damage to the surrounding healthy cells after TPE-PDT.